Respuestas

2013-04-21T19:57:27+02:00

a) y=6, 0, -2, -4

b) -4, 5, 8, 11

c) 3, 0, -1, -2

d) 6, 0, 2, 6

  • Usuario de Brainly
2013-04-21T20:43:01+02:00

a) y= -2x

y = - 2 (-3)

y = 6

 

y = -2 (0)

y = 0

 

y = -2.1

y = - 2

 

y = -2.2

y = -4

 

b) y = 3x+5

y = 3(-3)+5

y = -4

 

y = 3(0) +5

y =5

 

y= 3(1)+5

y = 8

 

y = 3(2) +5

y = 11

 

c) y =-x

y = 3

 

y= 0

 

y = 1

 

y= 2

 

d) y =x(x+1)

y = (-3)(-3+1)

y = 6

 

y = 0(0+1)

y = 1

 

y =1 (1+1)

y = 2

 

y= 2(2+1)

y = 6

 

espero que te sirva, salu2!!!!